2003
DOI: 10.1385/jmn:20:2:141
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PACAP In Gonadotropic Hormone Secretion at Hypothalamic and Pituitary Levels

Abstract: The presence of pituitary adenylate cyclase-activating polypeptide (PACAP) and its mRNAin the three levels of the hypothalamo-hypophyseal-ovarian axis was previously demonstrated using immunohistochemistry, in situ hybridization, and reverse transcriptase polymerase chain reaction (RT-PCR). In the hypothalamus, PACAP is present in neuroendocrine effector cells and in the median eminence. In the anterior pituitary and ovary, PACAP is transiently present during the proestrous stage of the estrous cycle. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…PACAP occurs in two forms: 27 and 38 amino acid residues. Several subsequent studies have shown the role of PACAP not only in the regulation of pituitary hormone secretion but also in other reproductive functions (Counis et al 2007;Isaac and Sherwood 2008;Koves et al 2003;Sherwood et al 2007;Szabo et al 2002). PACAP is present in the uterus, where it supposedly plays a role in muscle contraction and blood supply (Steenstrup et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…PACAP occurs in two forms: 27 and 38 amino acid residues. Several subsequent studies have shown the role of PACAP not only in the regulation of pituitary hormone secretion but also in other reproductive functions (Counis et al 2007;Isaac and Sherwood 2008;Koves et al 2003;Sherwood et al 2007;Szabo et al 2002). PACAP is present in the uterus, where it supposedly plays a role in muscle contraction and blood supply (Steenstrup et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…PACAP modulates gonadotropin biosynthesis and secretion, acting both alone and in concert with GnRH. Although less potent than GnRH, PACAP has been demonstrated to increase secretion of LH, FSH, and free ␣-subunit by perifused primary pituitary cells (5)(6)(7). The stimulatory effects of PACAP on LH secretion have been confirmed in vivo (8).…”
Section: Discussionmentioning
confidence: 98%
“…PACAP and its receptors are expressed in multiple tissues, including the central and peripheral nervous systems, smooth muscle of the lung and intestinal tract, and endocrine organs such as the placenta, adrenal, parathyroid, and endocrine pancreas; however, it is found most abundantly within the hypothalamic-pituitary-gonadal (HPG) axis (3,4). Reproductive functions include modulation of gonadotropin biosynthesis and secretion within the anterior pituitary gland, both alone and in concert with GnRH, as well as regulation of gonadal development and function (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…In support of this notion is that central injection of this peptide into male rat hypothalamus provoked an increase mRNA levels of gonadotropin-releasing hormone (GnRH) and somatostatin (SS) in the periventricular nucleus [164]. It was also observed that administration of PACAP into neonatal female causes a delay in puberty whereas central injection of the peptide into female rat before a critical period of proestrus stage controls ovulation via CRF and endogenous opioids [165]. In addition, PACAP through PAC1-R may play to regulate GnRH synthesis by the stimulatory feedback of progesterone [166].…”
Section: Actions In the Hypothalamusmentioning
confidence: 95%